Loschmidt echo and time reversal in complex systems - Alfieri, Arsenio Enrique (2016)
Goussev A, Jalabert RA, Pastawski HM,Wisniacki DA. 2016 Loschmidt echo and time reversal in complex systems. Phil. Trans. R. Soc. A 374: 20150383. http://dx.doi.org/10.1098/rsta.2015.0383 Echoes are ubiquitous phenomena in several branches of physics, ranging from acoustics, optics, condensed matter and cold atoms to geophysics. They are at the base of a number of very useful experimental techniques, such as nuclear magnetic resonance, photon echo and time-reversal mirrors. Particularly interesting physical effects are obtained when the echo studies are performed on complex systems, either classically chaotic, disordered or many-body. Consequently, the term Loschmidt echo has been coined to designate and quantify the revival occurring when an imperfect time-reversal procedure is applied to a complex quantum system, or equivalently to characterize the stability of quantum evolution in the presence of perturbations. Here, we present the articles which discuss the work that has shaped the field in the past few years.